Traditions et modernités : Eliot face à la temporalité française - William Marx (Itinéraires)
Why is the concept of modernism so unusual in French literature, unlike English and American literature? Why is the concept of classicism so usual in French literature, but not in Anglo-American literature? Our hypothesis is that both questions are connected: there are two different modernisms because the two literatures have radically different visions of time and of their own past. We try to prove that hypothesis through a study of T. S. Eliot’s and The Criterion’s complicated and ambiguous relationship with La Nouvelle Revue française.